Surface modification of hydrogels based on poly(2-hydroxyethyl methacrylate) with extracellular matrix proteins - Brynda, Eduard; Houska, Milan; Kysilka, Jirí; Prádný, Martin; Lesný, Petr; Jendelová, Pavla; Michálek, Jirí; Syková, Eva (Journal of materials science. Materials in medicine, 2009)
Infrared attenuated total reflection spectroscopy was used for in situ observation of the deposition of collagen I on poly(2-hydroxyethyl methacrylate-co-methacrylic acid, 2.9%) hydrogels and subsequent attachment of laminin or fibronectin on the collagen surface. While there was no adsorption of collagen dissolved in an acid solution on the hydrogel surface, it deposited on the surface at pH 6.5. The collagen layers with attached laminin or fibronectin were stable on hydrogel surface in physiological solution. The modification with collagen and particularly with collagen and laminin or fibronectin allowed the adhesion and growth of mesenchymal stromal cells and astrocytes on the hydrogel surface.
Keywords: mikroskopie atomárních sil; Extracellular Matrix Proteins; Hydrogels; Polyhydroxyethyl Methacrylate; polyhydroxyethylmethakrylát; extracelulární matrix - proteiny; spektroskopie infračervená s Fourierovou transformací; povrchové vlastnosti; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Spectroscopy, Fourier Transform Infrared; Microscopy, Atomic Force; Surface Properties; hydrogely